STRATEGI PENINGKATAN PRODUKSI SUBSEKTOR TANAMAN PANGAN DI KABUPATEN KUDUS - Fatimah, Fatimah; DM, Ida Hayu (Journal of Public Policy and Management Review, 2016)
The purpose of this study is to analyze the strategy of increasing crop production in Kudus regency by using internal and external environments analysis of organization. The result of analysis aimed to find the supporting and restricting factors faced by local government for increasing crop production in Kudus. In analizing the internal and external factors of this issue, researcher used SWOT Analysis (strenghts,Weakness,Opportunities, Treats). The research uses qualitative methods, defined by using information from Kudus of Agricultural and Fisheries Department and crops farmers in Kudus. The result of this research showed that Kudus regency has some potentional resources including fertile soil, capable human resources, supporting budget and policy by central government to support regional crop production. In other hand, local government also faced some restricting factors including climate change, political issue and industrial growth which affect local government will. By this research, it is very important to formulate some new recommended strategies for local government. The recommendations expected to help local government to increase crops production in Kudus.